Hedonic house price indices for Malta: A mortgage-based approach - Reuben Ellul; Jude Darmanin; Ian Borg (Central Bank of Malta, 2019)
This paper makes use of a novel dataset derived from mortgage contracts granted by the major lending institutions in Malta. This contains information about house prices and a number of important property characteristics. Together with geographic and sociodemographic variables, this information allows the computation of a range of hedonic house price indices for Malta for the period 2010-2017. In general we find that growth in house prices remained relatively muted over the period 2011-2014, ranging between 1.0% and 2.0%. House prices picked-up markedly after 2015, averaging between 4.5% and 7.5%. In particular, house price growth peaked in 2017, at between 10.1% and 11.0%. Although the general evolution of the hedonic house price indices calculated in this study are broadly similar to the indices computed by the contract-based index produced by the National Statistics Office and the advertised-based index produced by the Central Bank of Malta, there are some divergences. These differences can be attributed to changes in property characteristics.
Keywords: C4; E3; R3; R31; 330